Field Investigation of Blasting-Induced Vibration in Concrete Linings during Expansion of Old Highway Tunnel - Ya-Qiong Wang; Lin-Jin Gong; Nan-Nan An; Xing-Bin Peng; Wei Wang; Zhi-Feng Wang (Advances in Civil Engineering)
Numerous mountain highway tunnels in China do not satisfy the current traffic design standards and therefore need to be rebuilt or expanded. The drilling-blasting method is the primary method employed in China for expanding mountain highway tunnels, and it is crucial to monitor the vibrations caused by blasting. This study conducted a field investigation of the vibrations caused by blasting during the expansion of Yujiaya tunnel, which was built in 1999. The blasting-induced vibrations in the new and old concrete linings were monitored and analyzed during the expansion. The measured values of the peak particle velocity (PPV) varied within the range of 0.097–8.246 cm/s. The attenuation law of the PPV was determined via a regression analysis using Sadovsky’s empirical formula. The relationship between the main vibration frequency and the distance from the blasting source was expressed as a power function. Finally, the safety distances of the concrete linings subject to blasting vibrations were analyzed and discussed.